Gentoo pupils - Peter W. Hadden; Misha Vorobyev; Stephanie B. Cassidy; Akilesh Gokul; Samantha K. Simkin; Henry Tran; Charles N.J. McGhee; Jie Zhang (2022)
Part of a collection contains raw data obtained from in vivo and post mortem examination of the eyes of little penguins (Eudyptula minor) from Auckland, New Zealand, as well as captive king (Aptenodytes patagonicus) and gentoo penguins (Pygoscelis papua) descended from animals living on South Georgia. Included are A & B ultrasound recordings, corneal topography, photographs taken during keratoscopy, anterior segment optical coherence tomography scans and recordings made of the pupil of king, little and gentoo penguins.